Espaços coletivos de trabalho: entre a produção e a reprodução - Viviane Zerlotini da Silva (2014)
In order to produce their spaces groups of associated work adopt another rationality in spatial organization, not founded only in productivist bases. The reproductivist rationality includes traces of autonomy because it does not separate living and work spaces. Nevertheless, in technical and general common sense prevails the ideas of separation and functionalization of spaces, as bourgeois ideology conceives and modern architecture reinforces, contributing to the individual away from the public sphere. In turn, the associated work groups face limitations in the production of their space concerning the scarcity of resources, limited access to information and external determinations of market competition. The challenge of those groups and the theoretical and practical proposals that claim to favor them is to overcome the pseudo-alternative, previously defined by the vulnerability and insecurity they are submitted to. This research seeks to identify the conceptual basis of the tools mediations or interfaces of spatiality, that can leverage the features of autonomy and self-management already present in the production of space by associated workers, having for the horizon the free association of producers and breeders and the reproduction take precedence over production, in the sense of being the principal basis of the existence of society. In order to enhance the traits of autonomy and overcome oppressive gender and work relations, technicians busy with the collective must understand deeply, and critically, the advantages and small gains in autonomy of socio-spatial arrangements established by the collective, and they are minimally alternative to conventional arrangements, such as proximity or coincidence between residence and work, the relations of proximity between the group members, non-hierarchical relationships, horizontal organization of work of reproduction and production, cohabitation of the extended family, the useful effects of social workforce of reproduction and production, the combination of various scales of action, the development of effective capabilities of individuals, the free exchange of ideas, collective ownership of land and its means of production and production of political space.